Test beam results from the CLEO III LiF-TEA RICH - Artuso, M; Azfar, F; Efimov, A; Kopp, S; Mountain, R; Schuh, S; Skwarnicki, T; Stone, S; Viehhauser, G; Anderson, S; Smith, A; Kubota, Y; et al. (1998)
The CLEO collaboration is preparing a major upgrade of its present detector including a RICH detector for particle identification. This subdetector system follows the 'proximity focussing' design and uses Lithium Fluoride (LiF) crystal radiators and MWPCs filled with a CH4/TEA gas mixture. Part of the radiator crystals will have the new 'sawtooth' geometry. We have tested the first two of the 30 detector modules together with the first radiator crystals in a muon halo beam at Fermilab. For the measurement of the Cherenkov angle we obtain a single photon measurement error of 13.5 mrad for the conventional planar radiator. With 14 detected photons we find a resolution per track of 4.5 mrad. In the first measurement ever of a 'sawtooth' radiator we achieve a resolution of 11.8 mrad for single photons and 4.8 mrad per track for 12.3 detected photons with a reduced geometric acceptance. These results fulfill CLEO III requirements. (C) 1998 Elsevier Science B.V. All rights reserved.